Trend Analysis in Sales Forecasting and Decision Support Systems AHP Method on the Selection of Types of Motorcycles PT. AHM - Fikri, Akhsanul; Mustikasari, Metty (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
During the current Covid-19 pandemic, it has a direct impact on decreasing motorcycle sales at PT. Astra Honda Motor in large enough numbers, resulting in losses for the company. This study aims to analyze the forecasting of motorcycle sales in the future and supported by a decision support system in selecting the type of motorbike that consumers are most interested in. The method used in this research is the Trend method and the Analytical Hierarchy Process (AHP) method. The results of this study are based on the mean square error analysis, sales forecasting method at PT. Astra uses exponential trend analysis. The results of forecasting sales for the next 2 periods using the exponential trend analysis method are 2,715,032 units and 2,671,937 units, the sales levels tend to be the same as sales in the 2020 period. Meanwhile, the results of the decision support system analysis use the Analytical Hierarchy Process method (AHP), in choosing the type of motorbike that consumers are most interested in is an automatic motorbike at 0.63 with the preferred alternative is the fuel consumption aspect of 0.36.